Genetic Variation at Microsatellite Loci in Odorrana hosii (Boulenger, 1891) - Djong Hon Tjong; Anugrah Viona Agesi; Dewi Imelda Roesma (Biogenesis: Jurnal Ilmiah Biologi, 2020)
The true frog species, Odorrana hosii, found in West Sumatera Indonesia, has high morphological differentiation and also estimated has high genetic variation. A total of 35 O. hosii at a seven location have analyzed using DNA microsatellite markers. Genetic variation of five microsatellite loci provided the highest value of expected heterozygosity (He) for the population in Padang (He= 0.618), while the lowest was the population in Merapi (He= 0.427). There are genetic differences in moderate levels among populations of O. hosii in West Sumatra (FST= 0.108) with inbreeding intrapopulation value (FIS= -0.559), and high value of gene flow among the populations (Nm = 2.061). This study becomes the first molecular data for establishing effective population management conservation.